The effect of maximal speed ability, pacing strategy, and technique on the finish sprint of a sprint cross-country skiing competition - Haugnes, P.; Torvik, P.-Ø.; Ettema, G.; Kocbach, J.; Sandbakk, O. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To investigate the contribution from maximal speed (Vmax) and %Vmax to the finish sprint speed obtained in a cross-country sprint in the classical and skating style, as well as the coinciding changes in kinematic patterns and the effect of pacing strategy on the %Vmax. Methods: Twelve elite male cross-country skiers performed two 80-m Vmax tests on flat terrain using the classical double-poling and skating G3 techniques, followed by 4 simulated 1.4-km sprint time trials, performed with conservative (controlled start) and positive (hard start) pacing strategies in both styles with a randomized order. In all cases, these time trials were finalized by sprinting maximally over the last 80 m (the Vmax section). Results: Approximately 85% of Vmax was obtained in the finish sprint of the 1.4-km competitions, with Vmax and %Vmax contributing similarly (R2 = 51-78%) to explain the overall variance in finish sprint speed in all 4 cases (P < .05). The changes in kinematic pattern from the Vmax to the finish sprint included 11-22% reduced cycle rate in both styles (P < .01), without any changes in cycle length. A 3.6% faster finish sprint speed, explained by higher cycle rate, was found by conservative pacing in classic style (P < .001), whereas no difference was seen in skating. Conclusions: Vmax ability and %Vmax contributed similarly to explain the finish sprint speed, both in the classic and skating styles, and independent of pacing strategy. Therefore, sprint cross-country skiers should concurrently develop both these capacities and employ technical strategies where a high cycle rate can be sustained when fatigue occurs.